Development and Factor Structure of the School Counselor Noncognitive Skills Scale: High School Students Perceptions' of Noncognitive Skills Services. Issue 1 (4th March 2022) - Ohrt, Jonathan H.; Deaton, Jennifer; Gonzales, Shelby; Guest, Jessie
School counselors play an integral role in fostering students' noncognitive skills (e.g., social/emotional skills, mindsets) identified within the American School Counselor Association Mindsets & Behaviors Standards. We analyzed responses from a sample of 1484 high school students to explore the factor structure of the School Counselor Noncognitive Skills Scale (SCNSS). Results of an exploratory and confirmatory factor analysis yielded a three-factor solution: (a) Values and Decision Making, (b) Social/Emotional Skills, and (c) Future Planning. We discuss the rationale for the SCNSS in relation to evidence-based school counseling, describe the development and factor structure of the SCNSS, and offer implications for school counselors and future research.